PERSEBARAN TUMBUHAN OBAT PASAKBUMI (Eurycoma longifolia Jack.) DI JALUR UTAMA PATROLI TAMAN HUTAN RAYA (TAHURA) SULTAN SYARIF HASYIM PROVINSI RIAU - Aripan Yunas; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Taman Hutan Raya Sultan Syarif Hasyim (Tahura SSH) is a monument of natural forest in Riau province. Tahura SSH has kind of plants that have benefit medicinal. One of kind medicinal plants in Tahura SSH and has benefit is pasak bumi plant. The purpose this research to know distribution of pasak bumi in the main line patrol Tahura SSH in Riau province. This research using census method to make line transect. Using the analysis of Morisita index as a form of pasak bumi plant distribution along the Tahura Sultan SyarifHasyim’s mainline patrol formed a clustered pattern with values >1 for the right side of the line 5,78 and 4,90 for the left side of the line. Keywords: Distribution pattern, Medicinal plant, Pasak bumi, the main line patrol,Tahura